Screening of small molecules using the inhibition of oligomer formation in α-synuclein aggregation as a selection parameter - Roxine Staats (Nature Portfolio, 2020)
Promising treatments for neurogenerative disorders may involve targeting kinetic intermediates, including α-synuclein oligomers. Here a kinetic method for quantifying oligomer populations is used to screen small molecule inhibitors of oligomerisation and gain mechanistic insight into their modes of action.